Pilot Results for ECoLoGiC-Tx: A New Conversation-Level Intervention Improving Language in People With Moderate to Severe Aphasia. - Leaman, Marion C.; Edmonds, Lisa A. (American Journal of Speech-Language Pathology, 2024)
Purpose: This study reports pilot data for a novel intervention, ECoLoGiC-Tx, delivered to four people with moderate to severe aphasia. ECoLoGiC-Tx addresses language and communication in unstructured, participant-led conversation. The speech-language pathologist (SLP) uses a framework to choose turns that facilitate a social interaction. When communication breakdown occurs, the SLP implements a least-to-most hierarchy to maximize the people with aphasia's (PWA's) independence in self-repair. ECoLoGiC-Tx draws its theoretical underpinnings from conversation analysis and theories of rehabilitation, including principles of complexity, neuroplasticity, and learning. Method: Four PWA attended 60-min sessions twice weekly for 10 weeks. Assessment occurred at pretreatment, posttreatment, and 6-week maintenance. Outcomes included established discourse measures for conversation and monologue, tests of language and functional communication, and patient-/family-reported outcome measures (P/FROMs). Discourse samples were collected three times per assessment. Interrater reliability and fidelity for assessment and treatment procedures are reported. Results: Participants presented with Broca's aphasia (one moderate, one severe) or conduction aphasia (one moderate, one severe). Each demonstrated improvements in discourse, test batteries, and P/FROMs. They all demonstrated reduced aphasia severity measured by the Western Aphasia Battery-Revised at posttreatment or maintenance. Change in conversation and monologue was robust for three participants, but was mixed for one person (P1: moderate Broca's aphasia). P/FROMs indicated improvement at posttreatment and maintenance for all participants. Most treatment gains were maintained at 6-week follow-up. Conclusions: This study provides promising results for ECoLoGiC-Tx to improve language function of people with chronic moderate to severe aphasia. Generalization occurred to tests, functional communication, spontaneous conversation, and structured monologue tasks.